Comparative efficacy of once-weekly semaglutide versus SGLT-2 inhibitors in patients inadequately controlled with one to two oral antidiabetic drugs: a systematic literature review and network meta-analysis. Issue 7 (23rd July 2019) - Kanters, Steve; Wilkinson, Lars; Vrazic, Hrvoje; Sharma, Rohini; Lopes, Sandra; Popoff, Evan; Druyts, Eric
Abstract : Objective: To determine the comparative efficacy of once-weekly semaglutide relative to sodium-glucose cotransporter 2 inhibitors (SGLT-2is) licensed in Europe and North America among patients with type 2 diabetes (T2D) inadequately controlled with 1–2 oral antidiabetics (OADs), using a network meta-analysis (NMA). Design systematic review and network meta-analysis. Data Sources EMBASE, MEDLINE and CENTRAL were searched from January 1994 to August 2017. Methods: Randomised controlled trials with ≥20 weeks of treatment evaluating once-weekly semaglutide or SGLT-2is. Primary outcomes included change from baseline in: HbA1c, weight, systolic blood pressure, postprandial blood glucose and fasting plasma glucose. Fixed-effect and random-effect Bayesian NMA were used to indirectly compare treatment effects at 26 (±4) weeks. Metaregression and sensitivity analyses were conducted. Model selection was performed using the deviance information criterion and consistency was assessed by comparing indirect (edge-splitting) to direct evidence. Results: Forty-eight publications representing 21 trials were included. The mean differences (MD) in change from baseline in HbA1c of once-weekly semaglutide 1.0 mg versus SGLT-2is ranged from −0.56% for canagliflozin 300 mg (95% credible interval (CrI): −0.76 to −0.33%), to −0.95% for dapagliflozin 5 mg (95% CrI: −1.20 to −0.69%). The MD in change from baseline in weight of once-weekly semaglutide 1.0 mg versus SGLT-2is ranged from −1.35 kg for canagliflozin 300 mg to −2.48 kg for dapagliflozin 5 mg, while change from baseline in fasting plasma glucose ranged from −0.41 mmol/L for canagliflozin 300 mg to −1.37 mmol/L for dapagliflozin 5 mg. Once-weekly semaglutide was not statistically differentiable than all SGLT-2is in reducing systolic blood pressure. NMA was not feasible for postprandial blood glucose and safety outcomes. Conclusion: Once-weekly semaglutide demonstrated statistically significant and clinically meaningful reductions in HbA1c and body weight in T2D patients inadequately controlled with 1–2 OADs compared to all SGLT-2is licensed in Europe and North America.